Pregnancy rate per cycle is heritable and reduces with cycle in naturally mated tropically adapted beef cows. Issue 10 (22nd July 2021) - Fordyce, Geoffry; Williams, Paul; Corbet, Nicholas J.; Costilla, Roy; McGowan, Michael R.
Abstract: Pregnancy in cattle is the outcome of the complex process of initiation of cycling, fertilization, maternal recognition of pregnancy and foeto‐placental development. Though much is known about initiation of cycling and associated risk factors, there are virtually no data on pregnancy rate per cycle for naturally mated cattle, especially for extensively managed, tropically adapted genotypes, which this study aimed to determine. Tropical composite ( Bos indicus and African Sanga crosses with Bos taurus ) and Brahman cattle ( n = 2, 181) of known pedigree in four‐year groups at four sites were mated annually for 84 days. Body condition, ovarian function, pregnancies, calving and lactation were monitored through six full reproductive cycles using 4–8 weekly ultrasound of the reproductive tract outside the calving period and daily monitoring during calving. From this, dates of commencement of cycling and conception in each year were estimated for each animal, enabling calculation of established pregnancy for consecutive 21‐day periods while cycling and of pregnancies within four months of calving while lactating (P4M). Pregnancy per 21‐day period (cycle) during mating for cycling animals averaged 63%, 71%, 41% and 28% in four consecutive cycles. Pregnant per cycle was 2%–11% higher in tropical composites than in Brahmans. The only other consistently significant risk to becoming pregnant was if cycling commenced later than three weeks before mating commenced. P4M averaged 62% and was lower for cows in sub‐optimal body condition and in first‐parity and later‐calving cows. Pregnant per cycle was moderately heritable ( 20%), while heritability was moderate to high (33%) for P4M. Selection for pregnant per cycle could be achieved indirectly by selection for P4M, a trait that is readily measured.